Translating Politeness in Bilingual English-Spanish Business Correspondence - Fuertes-Olivera, Pedro; Nielsen, Sandro (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractPoliteness is an important element in interlingual business communication. Translators use bilingual dictionaries as tools helping then in business discourse across cultures, but dictionaries do not contain the relevant pragmatic information. The functions of dictionaries are used to determine which pragmatic information types are needed when translating business letters. The analysis focuses on a Spanish-English business dictionary and its treatment of politeness in special sections dealing with business correspondence. The findings show that the treatment is insufficient, because users’ business-language competence does not enable them to express the right level of politeness. Bilingual dictionaries should offer a systematic treatment of cultural and genre-specific means of expressing politeness in contrastive, informative texts showing the specific uses of politeness in business discourse. Finally, proposals on what to include and how this can be done are made, with a view to helping translators.